Hydrodynamics of laminar pipe flow through an extended partial blockage by CFD - Nuno M. C. Martins; Dídia I. C. Covas; Silvia Meniconi; Caterina Capponi; Bruno Brunone (Journal of Hydroinformatics, 2023)
In this paper, an advanced three-dimensional (3D) computational fluid dynamics (CFD) model is used to analyse the steady-state hydrodynamics of laminar flow through an extended partial blockage (PB) in a pressurised pipe. PB corresponds to one of the main faults affecting pipelines. In fact, it reduces its carrying capacity with economic consequences, and as it does not give rise to any external evidence, its detection can be very challenging. The performance of the model is evaluated by comparing the numerical results with the available experimental data from the literature. Subsequently, the velocity and pressure distributions are analysed, and the main features of the flow field are described in terms of both local and global dimensionless parameters. Furthermore, the behaviour of the discharge coefficient is also investigated. The obtained results confirm that steady-state measurements can identify the presence of PB and follow its evolution over time but cannot detect its location and size. On the other hand, the location and severity of PBs can be provided by means of transient tests. HIGHLIGHTS Analysis of the steady-state laminar flow through an extended partial blockage.; Validation of a 3D CFD model of an extended partial blockage with experimental data from the literature.; Velocity and pressure fields characterisation around an extended partial blockage.; Characterisation and evaluation in time of an extended partial blockage.; Hydrodynamics of a flow through an extended partial blockage.;